ITERATIVE PROBABILISTIC SOLUTION METHOD OF INTERSECTORAL BALANCE LINEAR EQUATION - Veronika S. Strelchenko; Igor V. Boguslavskiy (Advanced Engineering Research, 2011)
The new solution method for the systems of linear algebraic equations based on the application of the measure theory in the probabilistic space is stated. The possibility of its application for the solution of the equation of linear intersectoral balance is shown.